Elevated Plasma Levels of PAI-1 Predict Cardiovascular Events and Cardiovascular Mortality in Prevalent Peritoneal Dialysis Patients - ARIKAN, İZZET HAKKI; KOÇ, MEHMET; TUĞLULAR, ZÜBEYDE SERHAN (TAYLOR & FRANCIS LTD, 2009)
Background. Elevated plasminogen activator inhibitor-1 (PAI-1) levels are associated with increased cardiovascular (CV) risk in the general population. It has been shown that peritoneal dialysis (PD) patients have increased plasma levels of PAI-1. The aim of this study was to investigate whether PAI-1 independently predicted CV outcome in PD patients. Material and Methods. Seventy-two PD patients (53% females, mean age 49.9 +/- 16.1 years) were studied. Twelve patients who underwent kidney transplantation and 14 patients who transferred to hemodialysis during follow-up were excluded from the analysis. The remaining 46 patients (54% female, mean age 54 +/- 16 years, dialytic age 42 +/- 30 months) were followed a mean time of 45.4 +/- 19.4 months (range 8-71 months). Baseline PAI-1, clinical, and laboratory parameters were assessed in all patients. Survival analyses were made with Kaplan-Meier and Cox regression analysis, with all-cause mortality and CV mortality and CV events (CVEs) as clinical end points. Results. During the follow-up, 29 patients died (17 from CV causes), and 28 fatal and non-fatal CVEs were recorded. The patients were divided according to plasma PAI-1 levels (i.e., <= or >41 ng/mL). The significant independent predictors of all-cause of mortality were age (>60 years; p = 0.018), CRP (>5 mg/L; p = 0.015), and serum albumin (<3.5 g/L; p = 0.011). Multivariable Cox regression analysis showed that plasma PAI-1 >41 ng/mL was independently predictive of higher CV mortality (p = 0.021) and CVEs (p = 0.001). The only other independent predictor of CV mortality was only CRP (>5 mg/L; p = 0.008). Conclusions. Plasma levels of PAI-1 >41 ng/mL is a significant predictor of CV mortality and CVEs in PD patients.
Keywords: PAI-1; cardiovascular outcome; peritoneal dialysis; PLASMINOGEN-ACTIVATOR INHIBITOR-1; C-REACTIVE PROTEIN; ERYTHROPOIETIN THERAPY; MYOCARDIAL-INFARCTION; HEMODIALYSIS-PATIENTS; INSULIN-RESISTANCE; HEART-DISEASE; RISK-FACTORS; INFLAMMATION; ATHEROSCLEROSIS